Cumulative live birth rates according to the number of oocytes retrieved following the "freeze-all" strategy - Zhonghua Zhao; Hao Shi; Jing Li; Yile Zhang; Caihong Chen; Yihong Guo (BMC, 2020)
Abstract Background In recent years, some studies have shown that there is a positive association between the number of oocytes retrieved and the cumulative live birth rate (CLBR) after fresh and frozen cycles of one oocyte retrieval. However, almost no studies have examined the association between the number of oocytes retrieved and the CLBR when using the "freeze-all" strategy. We performed this study to investigate the effects of an extreme oocyte yield during the first "freeze-all" cycle on the cumulative live birth rate among patients younger than 35 years old. Methods This was a retrospective cohort study performed in a university-affiliated reproductive medicine centre. Data obtained from 3276 women aged younger than 35 years who underwent their first "freeze-all" cycle (IVF/ICSI) were collected between January 2009 and December 2016. In all, 5025 frozen cycles took place during the follow-up period from January 2009 to December 2018. Patients were divided into five groups according to oocytes retrieved (group 1: 4-10 oocytes; group 2: 11-20 oocytes; group 3: 21-30 oocytes; group 4: 31-40 oocytes; group 5: > 40 oocytes). The primary outcome was the cumulative live birth rate. Results Unadjusted results showed that the cumulative live birth rate significantly increased as the number of oocytes retrieved increased and reached up to 93.82% in cases with yields of 21-30 oocytes (P < 0.05), after which it did not have a significant increase (P > 0.05). After adjusting for confounders, our results showed that the number of oocytes retrieved is an independent positive predictor of cumulative live birth rate when using a "freeze-all" strategy. (P < 0.001). In addition, the fertilization rate and the gonadotropin dose also influenced the cumulative live birth rate (P<0.05). Conclusions Among women younger than 35 years old who underwent the "freeze-all" strategy, the number of oocytes retrieved positively correlated with the cumulative live birth rate. Taking both efficacy and safety into account, ovarian stimulation should be rational, and the upper limit of the oocyte yield should be no more than 30.